Two novel species of Vagicola (Phaeosphaeriaceae) from Italy - S. C. Jayasiri (2018)
© 2015. Phaeosphaeriaceae is a large and important family in the order Pleosporales, comprising economically important plant pathogens. Species may also be endophytes or saprobes on plant hosts. Two new species referable to Vagicola, Phaeosphaeriaceae are introduced in this paper based on analyses of LSU and ITS sequence data and their unique morphology. Most Phaeosphaeriaceae species grow on monocotyledons; Vagicola dactylidis and V. chlamydospora are also saprobic on grasses (Poaceae). Vagicola chlamydospora formed asexual structures in a culture. The new species are described and illustrated and compared with other taxa.